Binary Stars in the Milky Way Nuclear Stellar Cluster - Marklund,Arn (2024)
The Milky Way harbors a supermassive black hole (SMBH) at its dynamical center. Surrounding the SMBH is a dense nuclear star cluster (NSC) which is believed to include a binary population. Beyond $0.1pc$ from the SMBH, Eccentric-Kozoai Lidov oscillations are suppressed by general relativity precession, and the dynamical evolution of binaries are completely dominated by encounters with other stars in the NSC. At the same time, the velocity dispersion is set by the gravitational field of the SMBH, making it a unique laboratory to explore both processes and objects that are not seen elsewhere in the galaxy. In this thesis, I model the dynamical evolution of binary systems through repeated three-body encounters by utilizing the few-body code TSUNAMI. I find that binary mergers are predominantly induced by encounters driving the binary's eccentricities to near parabolic orbits. In some cases, binary mergers are instead induced through a collision; the coalescence of three stars which we refer to as a three-body pile up (3BPU). Using the smoothed-particle hydrodynamics (SPH) code PHANTOM I look at a subset of collisions, mergers and 3BPUs in more detail to understand the structure of the immediate remnants. I compare these to blue straggler stars (BSSs), red novae and the G-objects; stellar sources enshrouded by dust and gas that so far have only been observed in the Galactic Center. I find that remnants formed in 3BPUs are not very different from those formed in regular collisions and mergers apart from the additional mass that is retained. A rough estimate sets the 3BPU rate at $\sim 0.0017Gyr^{-1}$ ($\sim 0.00028Gyr^{-1}$) for a binary $0.1pc$ ($0.3pc$) from the SMBH. I conclude that all cases of collisions, mergers and 3BPUs reasonably match observations of red novae, and further support the idea that the G-objects are barely evolved merger remnants that do net yet appear as rejuvenated BSSs. Ignoring subsequent star formation episodes following the formation of the NSC, at $0.1pc$ ($0.3pc$) from the SMBH, the binary fraction for solar mass stars is at most 0.2% (1.4%) and made up of hard and moderately soft binaries at present day. This fraction is far too low to account for the number of observed G-objects, and suggests that if the G-objects are the result of binary mergers, they should have been formed following the recent star formation episode 4-6 Myr ago. This is consistent with the upper bound for the thermal timescale of the various merger remnants in my simulations - though it is most likely that the G-objects were formed $\lesssim 10^5$ yrs ago.
Keywords: stars: kinematics and dynamics; binaries: general; galaxy: nucleus; methods: numerical